2008
DOI: 10.1007/s11999-007-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After TKA for Patients With Juvenile Rheumatoid Arthritis

Abstract: Total

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
16
1
2
Order By: Relevance
“…The positive effect of TKA on QOL has been established in some studies (5,6,(12)(13)(14)(15) . Jolles and Bogoch (5) studied QOL after TKA among patients with juvenile rheumatoid arthritis and observed that the instruments commonly used for assessing the results following TKA did not have the capacity to gather information of importance for the patients in the group studied.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The positive effect of TKA on QOL has been established in some studies (5,6,(12)(13)(14)(15) . Jolles and Bogoch (5) studied QOL after TKA among patients with juvenile rheumatoid arthritis and observed that the instruments commonly used for assessing the results following TKA did not have the capacity to gather information of importance for the patients in the group studied.…”
Section: Discussionmentioning
confidence: 96%
“…In an attempt to fill this need, result evaluation systems that take into account the patients' general data have been developed. These include the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) (5,10) . Clinical assessments on patients' state of health often reflect the physician's perceptions of the disease, frequently without correlations with patients' own perceptions about their health (11) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations